Photogrammetry ‑based spatial analyses of settlements in Severynivka and Nemyriv - Ławniczak, Marcin (Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Prahistorii Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Wschodni, 2016)
During the Polish ‑Ukrainian archaeological project “Fortresses of Ukraine” it was proposed to study two of the most significant sites with the newest possible technology. The final decision was made to apply the digital photogrammetry that was acquired with the use of drones.
Ukrainian fortresses a study of a strongholds system from the early iron age in Podolia
Keywords: photogrammetry; Scythian time; hillfort; defensive structures; Early Iron Age; fortification